HYPOGLYCEMIC ACTIVITY OF NIDDWIN, A POLYHERBAL FORMULATION IN NORMAL RATS - T.Sruthi; D.Satyavati; Dasari, Rajneekar; V.Jyothi; P.Roshan Ali (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The present study was focused to evaluate the hypoglycemic activity of NIDDWIN, a polyherbal formulation in normal rats. Methods: Male Albino Wistar Rats (180-200gms) were divided into four groups of five animals each. Group-I was given aqueous suspension of 2percent gum acacia, Group-II was given aqueous suspension of NIDDWIN 50mg/kg, Group-III was given aqueous suspension of NIDDWIN 100mg/kg, Group-IV was given aqueous suspension of Glibenclamide 10mg/kg were given orally for 10days. The blood samples were collected before and after administration drugs at 0hrs, 2hrs, 4hrs, 6hrs, and 8hrs on 1st, 5th, and 10th days from retro-orbital sinus and serum was separated and estimated for glucose, cholesterol and triglycerides by using analytical method[1,2]. Results: NIDDWIN showed significant hypoglycemic activity at 4hrs on 1st, 5th, and 10th days was found to be effect in comparable with standard Glibenclamide 10mg/kg. Conclusion: NIDDWIN a polyherbal formulation concluded that it possesses hypoglycemic activity in normal rats and should be evaluated for its antidiabetic activity. Keywords: NIDDWIN, Glibenclamide, Glucose Kit, Cholesterol kit, Triglyceride Kit, UV-Spectrophotometer.